Sufi Springs: Air on an Oud String. Issue 1 (April 2015) - Rooney, Caroline
<x xml:space="preserve">Abstract</x> The initial part of Caroline Rooney's essay offers an incisive account of the author's experience of Cairo in the years leading up to the 2011 uprisings that led to the end of Hosni Mubarak's rule. Rooney's narrative evinces an active Downtown cosmopolitan spirit characterised by a burgeoning sense of 'audacity' in forms of arts activism, and its attendant collective spirit of perseverance that increasingly rendered ineffective the repressive manoeuvres of Egypt's disciplinary State. Criticising the impulse to construe the Egyptian revolution in terms of a mimetic desire for a secular democracy on Western lines, Rooney insists that the Arab uprisings consisted, in many respects, of a revolution against Western-style free market neoliberalism. Countering the perpetual cynicism attendant to the latter, Rooney argues, requires a form of politicisation that maintains 'the ongoing presence of the real as a matter of collective spirit' – one that can outlast the colonial interlude by resisting the absolutist self-assertion of market fundamentalism and its collusions with 'diplo-economic cosmopolitanism' as a mode of class-discriminatory privilege, as well as the compromising nature of right-wing Islam. Rooney moves on to locate a counter-movement based on an alternative form of consciousness that manifests itself 'as solidarity, as resoluteness, as genuine comradeship, as collective consciousness, as revolutionary faith and [as] festiveness.' In the last part of her essay, Rooney raises the intriguing case of Sufism, and specifically its mulid rituals and its important role in the Egyptian revolutionary effort, as a relational cultural mode that can survive the will-to-dominance as a persistent and liberatory collective gesture.